Sustainable injection moulding: The impact of materials selection and gate location on part warpage and injection pressure - Fawzi Belblidia (Sustainable Materials and Technologies, 2015)
This paper presents an approach of how warpage (i.e. part deflection) and injection pressure of an intricate geometry could be minimised by selecting an optimal thermoplastic material and injection gate location (through which the molten plastic flows into the cavity). The numerical analyses for mould filling considered four gate locations along with a PP (polypropylene), PS (polystyrene) and a fibre-filled PP material (each had different shrinkage characteristics, mechanical property and viscosity). Results of the cavity filling simulations indicated that (on average) the largest and smallest warpage was predicted with the PP and PS respectively. The warpage of the fibre-filled PP showed the most gate location dependent behaviour. In addition, the lowest injection pressure was associated with the fibre-filled PP. For reduced pressure, the best and second best solutions for gate location were the top and middle ones. In addition, specific attention was paid to differential fibre orientation, as one of the most important factors responsible for part warpage. In an attempt to maximise the part stiffness, the fibre-filled PP was selected. It became clear that the gate location affected the melt flow evolution and therefore the fibre orientation. Simulation results showed that bidirectional flow and asymmetrical fibre distribution was achieved with the gate positioned at the mid-section of the part. Unidirectional flow and therefore symmetrical fibre distribution could be achieved by placing the gate at the top section of the part. The injection moulding experimental utilised the fibre-filled PP along with the two aforementioned gate locations. It was discovered that warpage was present when the middle gate was applied, but it was successfully eliminated using the top gate location. It can be stated that differential fibre orientation did not cause warpage, but the asymmetrical distribution of fibre orientation did. The information discussed in the paper may be particularly useful in the early mould/part design stages when any modification can still be easily and cost-effectively implemented. An important finding is that the final gate location should only be chosen after the thermoplastic material properties and melt flow direction have been taken into account. The successful reduction of warpage and injection pressure may help to reduce the amount of production waste and energy consumption, ensuring defect-free sustainable manufacturing.